Metabolic disorder of nutrients—an emerging field in the pathogenesis of preeclampsia - Li, Shuyue; Zhu, Jie; Zhao, Ying; An, Ping; Zhao, Huanqiang; Xiong, Yu (Frontiers in Nutrition, 2025)
It is well acknowledged that metabolic disorder binds closely with preeclampsia, though some of the causal relationships are still ambiguous. This review systematically summarizes the metabolic characteristics of carbohydrates, lipids, amino acids, and glycans in preeclampsia, highlighting their roles in oxidative stress, trophoblast autophagy, inflammatory response, and vascular tone regulation. Key findings include upregulated glycolysis and impaired mitochondrial function contributing to ATP deficiency, dysregulated lipid metabolism exacerbating oxidative stress and vascular dysfunction, and amino acid imbalances disrupting immune responses and redox homeostasis. Emerging therapies, such as metformin and pravastatin, demonstrate potential in targeting these pathways for prevention and treatment. Here, we reviewed thoroughly the related literature with a view to delineating the potential association of nutrient metabolism with preeclampsia, so that we could explore a promising therapeutic approach.